Red algal diversity (Rhodophyta) from Peru based on molecular analysis - Calderon, Martha S.; Bustamante, Danilo E.; Boo, Sung Min (My University, 2020)
In Peru, an ongoing project has been to document the marine macroalgal biodiversity using molecular approaches because, to date, the Peruvian marine flora has been mostly characterized on the basis of morphological observations. We herein report on red algae collected along the coast of Peru, including specimens collected at historically important collecting sites, in order to provide a better understanding of Peruvian red algal diversity. Using phylogenetic analysis of rbcL DNA sequences, we report for the first time the occurrence of Nothogenia chilensis, Porphyra mumfordii, and Schizymenia dubyi in Peru. Results from molecular and morphological analysis of topotype material show that Chondracanthus glomeratus (M.Howe) Guiry is conspecific with C. chamissoi (C.Agardh) Kutzing. Both Rhodymenia howeana E.Y.Dawson and R. multidigitata E.Y.Dawson, Acleto & Foldvik are proposed to be later taxonomic synonyms of R. corallina (Bory) Greville. Future studies will reveal more diversity of red algae from Peru with special emphasis on members of the family Bangiaceae, Delesseriaceae, and Lithophyllaceae.
Keywords: marine algal flora; molecular taxonomy; new report; pacific south america; synonyms